CANSAT INTEGRATION USING MICROCONTROLLER - Muhammad Hafiz Bin Amir, Muhammad Hafiz (Universiti Teknologi Petronas, 2010)
This research emphasizes on the operation of CanSat which involves monitoring the temperature and pressure of the surrounding environment where the data can be transmitted almost instantaneously on demand. The satellites monitoring is done by using the accelerometer to determine the direction heading and the pressure sensor to determine the altitude.